Significant association between joint ultrasonographic parameters and synovial inflammatory factors in rheumatoid arthritis - Kondo, Yasushi; Suzuki, Katsuya; Inoue, Yumiko; Sakata, Koumei; Takahashi, Chihiro; Takeshita, Masaru; Kassai, Yoshiaki; Miyazaki, Takahiro; Morita, Rimpei; Niki, Yasuo; Kaneko, Yuko; Yasuoka, Hidekata; et al. (Arthritis research & therapy, 2019)
Ultrasonography (US) can directly demonstrate joint inflammation, including grayscale (GS) signs of synovial hypertrophy and power Doppler (PD) techniques to demonstrate increased blood flow and vascularization. Recently, echogenicity, especially hypoechoic synovium, has also been associated with local inflammatory activity. However, only a few studies have demonstrated correlation between histopathologic and immunopathologic evaluation and US findings. The aim of this study was to clarify whether joint US findings including synovial hypertrophy, vascularity, and echogenicity can accurately characterize synovial pathophysiology in patients with active rheumatoid arthritis (RA). A total of 44 patients with RA were included, both treated (n = 25) and untreated (n = 19) and scheduled for US examination of the knee joint with synovial fluid (SF) aspiration and two treated patients also underwent synovial biopsy. US images were quantitatively analyzed using grayscale assessment of synovial hypertrophy and PD for vascularity and echogenicity. Levels of nine SF cytokines and growth factors were also measured. Both US synovial hypertrophy and PD vascularity significantly correlated with SF inflammatory cytokine levels such as IL-6, IL-8, IL-1β and IL-10 in untreated patients. Angiogenic factors, including vascular endothelial growth factor (VEGF), only correlated with PD vascularity. In the treated patients, the associations between synovial hypertrophy and any cytokines were diminished, although synovial vascularity and echogenicity correlated with IL-6 and VEGF (p < 0.05). Histopathologic analysis revealed that hypoechogenicity of the synovium correlated with marked infiltration of lymphocytes and hypervascularity. We demonstrated the pathophysiological origins of US findings in the joint. The degree of US vascularity of the synovium correlated with local inflammatory cytokine levels and angiogenetic factors in patients with active RA. Synovial echogenicity, and not hypertrophy, correlated with inflammation, especially in treated patients with RA.